Frequency of Pulmonary Tuberculosis in Type 2 Diabetes on Insulin Therapy Presenting to MMC Mardan - Bahadur, Zeeshan; Rahman, Nabi; Farmanullah; Muhammad Abdullah (Indus Journal of Bioscience Research, 2025)
Background: Pulmonary tuberculosis continues to be a risky comorbidity among patients with type 2 diabetes mellitus, particularly those on long-term insulin therapy. Establishing the prevalence and risk factors of pulmonary tuberculosis in such individuals permits early prevention and detection, mostly in high-prevalence contexts. Objective: To determine the frequency of pulmonary tuberculosis in patients with type 2 diabetes on insulin therapy presenting to MMC Mardan. Study Design: Descriptive cross-sectional study. Duration and Place of Study: This study was conducted from January 2025 to May 2025, in the Department of Pulmonology, MTI-Mardan Medical Complex, Mardan. Methodology: A total of 113 patients aged 30–70 years with a diagnosis of T2DM on insulin therapy for at least 12 months were enrolled. Participants with at least two cardinal symptoms of tuberculosis underwent chest radiography followed by GeneXpert MTB/RIF assay for diagnostic confirmation. Results: The mean age was 49.23±11.61 years and the mean diabetes duration was 9.78±6.25 years. Overall frequency of pulmonary tuberculosis was 11.5% (n=13). Statistically significant associations were observed between PTB and rural residency (p<0.001), as well as smoking status (p<0.001). Conclusion: In our study, we concluded that pulmonary tuberculosis still poses a considerable risk among insulin-dependent type 2 diabetic individuals on insulin, particularly among rural residents and smokers.